The Diversity of Internet Memes Interpretations: A Discourse Analysis of Incongruity of Popular Memes Made by Indonesian Netizen - Putra, Rizky Anugrah; Triyono, Sulis (PAROLE: Journal of Linguistics and Education, 2016)
In the modern era, human has varied ways to communicate, interact, and express ideas. Using memes is one of contemporary human approaches to sending messages. However, similar to language, they have linguistics rules which have to be obeyed by the user. Memes also have its binding codes which are accepted by the memetic communities. This study is intended to reveal how widespread memes are violated by the netizen since there are diversities in using memes within Indonesian internet communities. To expose the violation phenomenon, the multimodal approach is conducted by using discourse analysis and social semiotics (Chandler, 2013) which focus on observing the visual and textual aspect of favorite memes. The paper claimed, that most of the Indonesian internet communities often force memes and use them in an inappropriate context.